Enhancing the enthalpic contribution of hydrogen bonds by solvent shielding. Issue 4 (28th August 2020) - Cramer, Jonathan; Jiang, Xiaohua; Schönemann, Wojciech; Silbermann, Marleen; Zihlmann, Pascal; Siegrist, Stefan; Fiege, Brigitte; Jakob, Roman Peter; Rabbani, Said; Maier, Timm; Ernst, Beat
Abstract : Altering local dielectric properties induced by solvent shielding, enhances polar interactions and leads to enthalpically driven recognition of polar substrates. Abstract : In biological systems, polar interactions are heavily burdened by high desolvation penalties resulting from strong solute–solvent interactions. As a consequence thereof, enthalpic contributions of hydrogen bonds to the free energy of binding are severely diminished. However, this effect is strongly attenuated for interactions within solvent-shielded areas of proteins. In microcalorimetric experiments, we show that the bacterial lectin FimH utilizes conformational adaptions to effectively shield its binding site from solvent. The transition into a lower dielectric environment results in an enthalpic benefit of approximately −13 kJ mol −1 for mannoside binding. However, this effect can be abrogated, if the hydrogen bond network within the binding site is disturbed by deoxygenation of the ligand. Conformational adaption leading to reduced local dielectric constants could represent a general mechanism for proteins to enable enthalpy-driven recognition of polar ligands.